Emergent transcatheter arterial embolization for norovirus‐associated life‐threatening ulcer bleeding to achieve successful hemostasis in 2‐year‐old boy. Issue 4 (13th May 2016) - Matsuoka, Wakato; Kaku, Noriyuki; Hirata, Yuichiro; Lee, Sooyoung; Akahoshi, Tomohiko; Sugimori, Hiroshi; Hayashida, Makoto; Souzaki, Ryota; Fujita, Norihiro; Asayama, Yoshiki; Taguchi, Tomoaki; Takada, Hidetoshi; et al.
Abstract : Case: We report a 2‐year‐old boy with duodenal ulcer with active bleeding that occurred as a result of norovirus gastroenteritis. On admission, the patient presented with shock accompanied with vomiting and melena. Abdominal contrast enhanced computed tomography scan showed signs of duodenal bleeding. Outcome: He was successfully treated with emergent transcatheter arterial embolization. After the treatment, endoscopic examination revealed duodenal ulcer and the stool norovirus antigen test was found to be positive. The patient recovered completely without any sequelae. Conclusion: Life‐threatening duodenal ulcer bleeding in children can be caused by viral gastroenteritis. When endoscopic therapy is unsuccessful or difficult, in cases of small children, angiographic intervention can be a safe alternative treatment option of gastrointestinal bleeding.